Inflammatory Malignant Fibrous Histiocytoma Associated with Leukemoid Reaction or Leukocytosis: A Comprehensive Review. (14th October 2012) - Hurtado-Cordovi, Jorge; Pathak, Prajwol; Avezbakiyev, Boris; Frieri, Marianne
Abstract : Inflammatory malignant fibrous histiocytoma (IMFH) associated with leukemoid reaction (LR)/leukocytosis is a rare entity. In this paper, we search PubMed for all known cases of IMFH associated with LR/leukocytosis in an attempt to draw conclusions about this variant's response to treatments and its pathophysiology. Medline electronic database was searched using key words such as malignant fibrous histiocytoma, leukemoid reaction, and leukocytosis. A total of 16 patients were found, twelve males (75%) and 4 female (25%), with a mean age of 62.6 years, ranging from 47 to 77. The mean survival was 770 days, ranging from 14 to 6570 days. Four patients were alive at last follow-up: 6570 days, 1095 days, 335 days, and 180 days, respectively. Of the 12 patients that expired, death occurred approximately 92 days after the onset of LR or leukocytosis, ranging from 3 to 334 days. We conclude that IMFH associated with LR/leukocytosis does not completely respond to chemoradiation. Overproduction of growth factors and cytokines by IMFH cells and their interactions with the inflammatory infiltrate seem to promote immunological effector cell's dysfunction and substantiate the development and growth of this neoplasm. A clear understanding of these molecular pathways is crucial in order to identify targets for potential therapy.